The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/biom10020275
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 5 Inhibitor Butyrolactone I Elicits a Partial Agonist Activity of Peroxisome Proliferator-Activated Receptor γ

Abstract: Adiponectin is an adipocyte-derived cytokine having an insulin-sensitizing activity. During the phenotypic screening of secondary metabolites derived from the marine fungus Aspergillus terreus, a poly cyclin-dependent kinase (CDK) inhibitor butyrolactone I affecting CDK1 and CDK5 was discovered as a potent adiponectin production-enhancing compound in the adipogenesis model of human bone marrow-derived mesenchymal stem cells (hBM-MSCs). CDK5 inhibitors exhibit insulin-sensitizing activities by suppressing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…We found that it exhibited significant anti-food allergic activities in vitro and in vivo [14]. Therefore, BTL-I has additive or synergistic therapeutic potential in diseases with multi-factorial etiologies, and provides a potential new insight to the prevention and treatment of food allergy diseases [15].…”
Section: Introductionmentioning
confidence: 84%
“…We found that it exhibited significant anti-food allergic activities in vitro and in vivo [14]. Therefore, BTL-I has additive or synergistic therapeutic potential in diseases with multi-factorial etiologies, and provides a potential new insight to the prevention and treatment of food allergy diseases [15].…”
Section: Introductionmentioning
confidence: 84%
“…Second, the structural stabilization of the Ω-loop, helix H3 and H11-H12 loop observed in the PPARγ Q286E structure would indirectly favor the active conformation ( Figure 2D and Figure S5). In some cases, PPARγ ligands such as partial agonists do not directly interact with helix H12 but induce the transactivation of PPARγ [39][40][41][42]. These ligands have been suggested to indirectly elicit the transactivation of PPARγ by stabilizing the helix H3 and Ω-loop via an alternate binding site.…”
Section: Discussionmentioning
confidence: 99%
“…The cloning, expression, purification and crystallization of human PPARγ LBD were mainly performed as previously reported [39]. In brief, PPARγ LBD (residues 195-477 in PPARγ1 numbering) was cloned into the expression vector pET-28b(+) (Novagen, Darmstadt, Germany) between Nde1 and Xho1 restriction sites containing an N-terminal His 6 tag (MGSSHHHHHHSSGLVPRGSH) and a thrombin cleavage site.…”
Section: Cloning Expression and Mutagenesismentioning
confidence: 99%
“…Recently, it was found to improve T2DM with potent TNF-α lowering properties through modulating gut microbiota in db/db mice [ 33 ]. The adiponectin production-enhancing activity of butyrolactone I was explained by its dual modulator activities as both a CDK5 inhibitor and a peroxisome proliferator-activated receptor γ partial agonist [ 34 ]. Additionally, both natural and synthetic analogues of butyrolactone I exhibited interesting biological activities, including anti-microbial and antitumor effects [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%